2006
DOI: 10.1177/154405910608500302
|View full text |Cite
|
Sign up to set email alerts
|

Protective and Destructive Immunity in the Periodontium: Part 2—T-cell-mediated Immunity in the Periodontium

Abstract: Based on the results of recent research in the field and Part 1 of this article (in this issue), the present paper will discuss the protective and destructive aspects of the T-cell-mediated adaptive immunity associated with the bacterial virulent factors or antigenic determinants during periodontal pathogenesis. Attention will be focused on: (i) osteoimmunology and periodontal disease; (ii) some molecular techniques developed and applied to identify critical microbial virulence factors or antigens associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
53
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 158 publications
(198 reference statements)
1
53
0
Order By: Relevance
“…In summary, our data suggest an inhibitory effect of hIL-10 on RANKL ϩ -Th-cell-mediated alveolar bone loss in an experimental periodontitis model which is correlated with the effects in successfully treated periodontal tissues in AgP. The present study illustrates and confirms the important role of gram-negative-pathogen-reactive RANKL ϩ Th cells coexpressing hIFN-␥, a signature Th1 cytokine, as a critical and positive cellular determinant in complex cytokine interactions and RANKL-RANK signaling for regulating osteoclastogenesis during periodontal disease progression in vivo (called RACIN [RANKL and cytokine interactions network] [34]). Thus, further understanding of these cellular and molecular interactions under pathological conditions may facilitate the development of novel therapeutic strategies and treatment protocols when dealing with inflammatory bone disorders such as human periodontitis in the future.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…In summary, our data suggest an inhibitory effect of hIL-10 on RANKL ϩ -Th-cell-mediated alveolar bone loss in an experimental periodontitis model which is correlated with the effects in successfully treated periodontal tissues in AgP. The present study illustrates and confirms the important role of gram-negative-pathogen-reactive RANKL ϩ Th cells coexpressing hIFN-␥, a signature Th1 cytokine, as a critical and positive cellular determinant in complex cytokine interactions and RANKL-RANK signaling for regulating osteoclastogenesis during periodontal disease progression in vivo (called RACIN [RANKL and cytokine interactions network] [34]). Thus, further understanding of these cellular and molecular interactions under pathological conditions may facilitate the development of novel therapeutic strategies and treatment protocols when dealing with inflammatory bone disorders such as human periodontitis in the future.…”
supporting
confidence: 79%
“…The study of osteoimmunology has demonstrated that host immune responses, especially T-cell immunity, play a pivotal role in regulating osteoclastogenesis and bone remodeling (26,(32)(33)(34)(35)36). The recently identified tumor necrosis factor (TNF) family molecule receptor activator of NF-B ligand (RANKL), its receptor RANK, and its natural antagonist, osteoprotegerin (OPG), have been shown to be the key regulators of bone remodeling involved in differentiation, activation, and survival of osteoclasts and osteoclast precursors (35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A central observation for osteoimmunology comes from the demonstration that skeletal homeostasis is dynamically influenced by the immune system and lymphocyte-derived cytokines are among the most potent mediators of osteoclast function and osteoclastogenesis (3,(5)(6)(7)(8)(9)(10). These mediators include receptor activator of NF-B ligand (RANKL) 2 (11,12), IFN-␤ (13-15), IFN-␥ (16 -18), TNF-␣ (19 -22), IL-1␤ (23)(24)(25)(26)(27), , , IL-17 (6, 36 -38), and IL-23 (6,38).…”
mentioning
confidence: 99%
“…Chronic periodontal involvement is an infectious, irreversible and destructive disease which has the contribution of the host immune system to be developed, since the production of cytokines such as interleukin-1 (IL-1), Tumor Necrosis Factor (TNF-) and prostaglandins by immune cells promotes bone resorption and destruction of conjunctive tissue by the action of osteoclasts (activated by IL-1 and TNF-) and metalloproteinases (activated by prostaglandins), respectively (Baker, 2000;Koop & Medzhitov, 2003;Teng, 2006;Alnaeeli et al, 2006).…”
Section: Introductionmentioning
confidence: 99%